2010
DOI: 10.1186/1471-213x-10-94
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression following induction of regeneration in Drosophila wing imaginal discs. Expression profile of regenerating wing discs

Abstract: BackgroundRegeneration is the ability of an organism to rebuild a body part that has been damaged or amputated, and can be studied at the molecular level using model organisms. Drosophila imaginal discs, which are the larval primordia of adult cuticular structures, are capable of undergoing regenerative growth after transplantation and in vivo culture into the adult abdomen.ResultsUsing expression profile analyses, we studied the regenerative behaviour of wing discs at 0, 24 and 72 hours after fragmentation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 78 publications
3
75
1
Order By: Relevance
“…This accurate sampling procedure made it possible to produce highly pure samples and a detailed comparison of gene expression changes in the early regenerating process. Several previous studies published transcriptome data from regenerating discs (17,19,33,34). However, comparing clusters I and III with these datasets, we found that rather few genes were shared with these studies.…”
Section: Upd Activates Jak/stat Signaling In Early Regenerating Discs Tomentioning
confidence: 67%
See 1 more Smart Citation
“…This accurate sampling procedure made it possible to produce highly pure samples and a detailed comparison of gene expression changes in the early regenerating process. Several previous studies published transcriptome data from regenerating discs (17,19,33,34). However, comparing clusters I and III with these datasets, we found that rather few genes were shared with these studies.…”
Section: Upd Activates Jak/stat Signaling In Early Regenerating Discs Tomentioning
confidence: 67%
“…Blanco et al (19) analyzed the transcriptome of regenerating wing discs at 24 and 72 h after fragmentation. The results of Blanco et al (19) uncovered the involvement of Notch signaling, cabut and absent, small or homeotic discs 2 in wound healing and regenerative cell proliferation.…”
mentioning
confidence: 97%
“…S3A). Using these reference controls and mRNA from whole wing imaginal discs, we detected elevated relative expression of genes that are upregulated after tissue damage, such as puckered and cabut (Blanco et al, 2010), or expressed only outside the ablation zone, such as teashirt (Wu and Cohen, 2002;Fig. S3B-D).…”
Section: Analysis Of the Role Of Trithorax During Regenerationmentioning
confidence: 99%
“…Two-color microarray design and analyses were carried out as previously reported (Beltran et al, 2007;Blanco et al, 2010). Total RNA was extracted from eyeantenna imaginal discs from wandering blue-gut staged early third instar larvae using the RNeasy Protect Mini Kit (Qiagen Inc., Valencia, CA, USA).…”
Section: Microarray Analysesmentioning
confidence: 99%